EFFORTS TO IMPROVE STUDENTS LEARNING OUTCOMES IN CLASS IV SCIENCE SUBJECT THROUGH THE INQUIRY LEARNING MODEL - Nurul Alfiya; Isna Ida Mardiyana; Astien Diena Koesmini; Rukmiyati Rukmiyati (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The use of conventional learning models in science learning continuously makes students often feel bored so that in the end it has an impact on science learning outcomes that are not good. The purpose of this study is to improve student learning outcomes in science learning through the inquiry learning model. The inquiry model is very suitable for problems that occur in the field because this model is very compatible with the nature and characteristics of science learning. This research is a class action research with the subjects involved are fourth grade students of Mlajah 2 Bangkalan Elementary School. The results obtained were an increase in learning outcomes from each cycle, which in the implementation of the first cycle of learning outcomes of students who were able to achieve KKM as many as 18 students who could percentage 42% and who did not complete as many as 25 students the percentage was 48% with an average value, ie 59.62. Whereas for cycle II student learning outcomes increased by obtaining an average score of 79 for students who completed as many as 35 percentages 81% and those who did not complete as many as 8 students percentage 19%. This shows that learning with this inquiry model can improve science learning outcomes for fourth graders of Mlajah 2 Bangkalan Elementary School.